Barbarians of wealth : protecting yourself from today's financial attilas - Franks, Sandy; Nunnally, Sara (Wiley, 2011)
"How the actions of a few in Europe destroyed the prosperity of the many (and how it?s happening again now in America). After the fall of the Roman Empire, vicious barbaric tribes including the Huns lead by Atilla, the Mongols, Charlemagne and the Vikings invaded Europe, plundering property and destroying homes. But, they didn?t just steal and destroy property in the villages; they also stole and destroyed any prosperity the villagers had previously enjoyed. What?s worse is the barbarians of the Dark Ages did all of this not out of any deeply held religious or political belief, but, rather, for the oldest reason in the book - their own personal financial gain. Some things never change. Barbarians of Wealth examines how the greedy, self-serving decisions of a select group of politicians and financial institutions negatively impacts the economy and, ultimately, destroys America?s prosperity and the American way of life. Compelling and engaging, the book details how Goldman Sachs peddled mortgage backed securities up and down Wall Street while secretly betting against their demise. Discusses how Sanford Weill, founder of Citigroup, spent $100 million lobbying for the repeal of the Glass-Steagall Act that prevented the merger of commercial and investment banks and got his way. Examines how Christopher Dodd, head of the U.S. Senate Banking Committee, has enriched himself while driving down the prosperity of his constituents. Offers up examples of other modern barbarians, including the Federal Reserve, Alan Greenspan, Hank Paulson, and Timothy Geithner. Highlights greed driven tactics of Wall Street corporations including JP Morgan, Merrill Lynch, and Salomon Brothers. Barbarians of Wealth is a timely must read for hard-working Americans concerned with their prosperity, as well as for those fascinated with the inner workings of Washington and Wall Street."